Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan Muslim pada Sa Bakery Ngawi - Sugeng Nugroho Hadi; Salihah Khairawati; Nur Hawa Meizara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Gaining loyal customers is a blessing for any business, including in the bakery business. The question then arises,